UMPSA organised Seminar on Training Methodology in TVET and Innovative TVET Teaching Methods - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 9 September 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) with a collaboration of Colombo Plan Staff College (CPSC) and the Ministry of Higher Education organised a five-day seminar on Training Methodology in TVET and Innovative TVET Teaching Methods starting today till 13 September 2024 at Banquet Hall, UMPSA Pekan.